Hermeneutics of 1 Thessalonians 4:13-18 and Death Rites According to Pamona Culture as a Strategy for Christian Religious Education for GKST Imanuel Taripa - Tololiu, Naomi H.M.; Weol, Wolter; Sellano, Semuel; Kambey, Ellen S. (International Journal of Education, Information Technology, and Others, 2023)
This research explores the understanding of death based on 1 Thessalonians 4:13-18, death rites according to Pamona Culture, and Christian religious education strategies for the GKST Immanuel Taripa congregation when confronting death. Utilizing qualitative methods with a descriptive analytical hermeneutic approach, the study employs historical-critical and reader response methods, focusing on the process and meaning of death in 1 Thessalonians 4:13-18 and Pamona cultural death rites. Phenomenological methods were also applied to capture subjective experiences. Data collection involved participant observation, interviews, and documentation studies.Findings reveal that Christ is perceived as the sole foundation and unwavering source of hope in the face of death. Belief in Christ's resurrection is seen as a solid foundation, offering profound meaning and spiritual tranquility. In Pamona culture, death rites play a crucial role in preserving local values, beliefs, and traditions, with deep symbolic meaning expressing love, togetherness, and cultural continuity. The integration of culture as a theological tool connects Pamona cultural values with Bible teachings and church life experiences. Christian Religious Education views culture as an opportunity to understand and appreciate community values, traditions, and wisdom. In facing death, the church implements education by combining Pamona cultural aspects into death rites, enriching these rites with comforting and affirming Biblical teachings. The research underscores the importance of incorporating local culture into Christian religious learning, advocating for conversations about death and culture that involve various generations through the intergenerational method.